Normative Data for Critical Speed and D' for High-Level Male Rugby Players. Issue 3 (March 2018) - Kramer, Mark; Clark, Ida E.; Jamnick, Nick; Strom, Cody; Pettitt, Robert W.
Abstract : Abstract: Kramer, M, Clark, IE, Jamnick, N, Strom, C, and Pettitt, RW. Normative data for critical speed and D' for high-level male rugby players. J Strength Cond Res 32(3): 783–789, 2018—The critical speed (CS) concept helps characterize the aerobic and anaerobic fitness of an athlete. Rugby players should, hypothetically, have modest CS values but extremely high curvature constant ( D' ) values, yet, normative data are currently unavailable. To develop normative data of CS and D' for high-level male rugby players, a total of 30 male rugby players were recruited from the Eastern Cape of South Africa. All subjects performed the running 3-minute all-out exercise test (3 MT) using global positioning system (GPS) technology to determine CS and D' . The GPS data were used to determine the total distance and velocities performed, and to examine for pacing effects. Summary statistics of mean ± SD are provided. High total running speeds for the initial 150 seconds ( S 150s = 5.79 ± 0.59 m·s −1 ), and total distance (3 MT distance = 871.5 ± 71.9 m) were observed. A total of 13 of 30 subjects surpassed the 300 m D' value (mean D' = 288.2 ± 49.1 m). The CS of the total group was 3.87 ± 0.55 m·s −1 . All 3 MT-derived data were categorized using standard nine (stanine) tables that allowed for the generation of normative data with which future performances, performances across similar sporting domains, and more accurate contrasts across the literature can be compared. Skewing of CS and D' was observed between forwards and backs, therefore, between-group differences in neither CS nor D' were observed ( p > 0.05). Comparisons with previous literature indicate that male rugby players have higher CS values than female rugby players. When compared with Olympic distance runners, male rugby players have markedly higher D' values and markedly lower CS values. The 3 MT provides a useful procedure for assessing and prescribing high-intensity interval training for rugby athletes.